Effectiveness of omega-3 fatty acid administration on completion rate of adjuvant chemotherapy for biliary tract cancer: study protocol for a single-centre, open-label, single-arm, historically controlled study. Issue 8 (9th August 2019) - Ueno, Kimihiko; Ajiki, Tetsuo; Tsugawa, Daisuke; Akita, Masayuki; Hashimoto, Yu; Awazu, Masahide; Mukubo, Hideyo; Komatsu, Shohei; Kuramitsu, Kaori; Terai, Sachio; Tanaka, Motofumi; Toyama, Hirichika; et al.
Abstract : Introduction: Multimodal treatment prolongs the survival of patients with biliary tract cancer (BTC). However, the chemotherapy choices for this disease are few, and completing each chemotherapy session is important. Adjuvant chemotherapy has been attempted for BTC, but has only had a 75% completion rate. Body weight loss and cholangitis are reasons for the interruption of chemotherapy. Previous reports suggested that nutritional intervention with omega-3 fatty acids maintained body weight and improved the completion rate for chemotherapy. Moreover, omega-3 fatty acids have an anti-inflammatory effect. Therefore, we theorised that omega-3 fatty acids would improve the completion rate of adjuvant chemotherapy in patients with BTC. The aim of this study is thus to evaluate the effectiveness of omega-3 fatty acids for patients planning adjuvant chemotherapy for BTC. Method and analysis: This study is a single-centre, open-label, single-arm, historically controlled study with a planned enrolment of 55 participants. Protocol treatment consists of four courses of S-1 adjuvant chemotherapy and an oral omega-3 fatty acid pharmaceutic adjuvant (LOTRIGA 2 g (Takeda Pharmaceutical Co.)), which includes 2 g of omega-3 fatty acids from day 1 until day 168 of the treatment period. The primary endpoint is the completion rate of four total courses of S-1. Secondary endpoints are postoperative cholangitis, time to recurrence or distant metastasis, changes in nutritional index, changes in the lymphocyte blast transformation test induced by phytohaemagglutinin, and concanavalin A and diamine oxidase serum activity during adjuvant chemotherapy. All adverse events will be evaluated. Ethics and dissemination: This protocol was approved by the Institutional Review Board of Kobe University Hospital. The findings from this study will be presented at national and international conferences and published in peer-reviewed journals. Trial registration number: UMIN000031247.